Techno-economic and risk analysis of closed-cycle gas turbine systems for sustainable energy conversion. - Osigwe, Emmanuel Ozioma (Cranfield University, 2018)
With renewed interest in research and development on the closed-cycle gas turbine technology, it is almost certain this energy conversion system may well emerge in the foreseeable future as a viable option in power generation and utility industry due to: (a) its easy adaptability to a wide spectrum of working fluids and heat sources (b) very high fuel utilization efficiency (c) reduction in pollution and energy consumption, (d) potential for high degree of availability, reliability and low maintenance cost and (e) high part-load performance characteristics. In Europe, power plants up to 50MWe have operated successfully on arrays of gaseous, liquid and solid fuels, and have demonstrated a high degree of availability and reliability, with both helium and air used as working fluids. Waste heat thermal energy from these plants, in form of hot water, has been utilized for industrial and urban district heating with results of over 80% fuel utilization efficiency met. However, despite the many advantages of the closed-cycle gas turbine system, it has not enjoyed widespread commercialization. This is because its features do not come free and the diffidence exploring the technology for future investment may be related to limited experience in design and operation for several variables such as working fluid options. Therefore, for the full potentials of the closed-cycle gas turbine to be realized, its suitability in the choice component design, cycle performance, economic potentials with minimum risk have to be proven in several off-setting conditions before any appropriate investment decision can be made. This research seeks to address the knowledge gap on the effect of selected working fluids such as helium, air, nitrogen, and carbon dioxide on the overall component design, cycle performance, and economics of the closed-cycle gas turbine power plant. To implement the research aim, a robust decision support framework for closed-cycle gas turbine using the Techno-economic, Environmental and Risk Analysis (TERA) method has been adopted in this research, as a multidisciplinary tool for strategic decision making in closed-cycle gas turbine technology investments. The governing principles of TERA arise from different module integration, which allows for design considerations and/or operating areas such as performance, environment, economics and risk analysis. In this research, each of the operating areas was modelled to achieve the central goal of the research. The results from the performance perspective show that the overall cycle efficiency of the closed-cycle gas turbine is maximum for working fluid with a high ratio of specific heats at lower pressure ratio. Also, the research shows that working fluid have great influence on design choice configuration, gas turbine component sizing and the initial cost of investment in closed-cycle gas turbine technology. In the economic assessment, competitive cost information was generated with helium showing a higher risk of investment due to its limited supply. Most significantly, the research provides a representative of trade-offs on the plant thermodynamic performance characteristics, economics and impact of working fluids on closed-cycle gas turbine system technology.
Keywords: Sustainable energy; competent design; TERA; cycle performance; working fluid; closed-cycle gas turbine